2011
DOI: 10.1590/s0100-204x2011000200008
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade genética de dourado utilizado em programas de repovoamento no rio Paranapanema

Abstract: Resumo -O objetivo deste trabalho foi avaliar a diversidade genética de um estoque de Salminus brasiliensis utilizado em programas de repovoamento do rio Paranapanema, por meio do marcador RAPD. Dez reprodutores (cinco machos e cinco fêmeas) e sua progênie (40 larvas e 40 alevinos) foram analisados. Os oito iniciadores analisados produziram 96 fragmentos, dos quais 81,2% foram polimórficos. Houve diferença significativa na frequência de 32 dos 96 fragmentos, com a presença de um fragmento exclusivo nos alevino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…Dominant marker in current assay proved efficient in the study of genetic variability. Other studies with the same marker for S. brasiliensis (ALMEIDA et al, 2013;GOMES et al, 2011GOMES et al, , 2013LOPES et al, 2007) and in other fish species (JACOMETO et al, 2010;, 2010LOPES et al, 2009;PAULA et al, 2006;POVH et al, 2008b) also gave positive results. In fact, dominant markers still have great possibilities of information for the initial review of genetic processes in natural populations or in fish stocks.…”
Section: Groupingmentioning
confidence: 80%
See 1 more Smart Citation
“…Dominant marker in current assay proved efficient in the study of genetic variability. Other studies with the same marker for S. brasiliensis (ALMEIDA et al, 2013;GOMES et al, 2011GOMES et al, , 2013LOPES et al, 2007) and in other fish species (JACOMETO et al, 2010;, 2010LOPES et al, 2009;PAULA et al, 2006;POVH et al, 2008b) also gave positive results. In fact, dominant markers still have great possibilities of information for the initial review of genetic processes in natural populations or in fish stocks.…”
Section: Groupingmentioning
confidence: 80%
“…Some studies on S. brasiliensis provided number of fragments and polymorphism very similar to current assay. Gomes et al (2011) studied restocking programs and detected 96 fragments analyzed for 8 starters and between 7 and 17 fragments per starter, of which 78 (81.25%) were polymorphic. Gomes et al (2013) obtained 105 amplified fragments (79 or 75.2% were polymorphic) from the same species captured in the transposition ladder in the Canoas I hydroelectric plant.…”
Section: Resultsmentioning
confidence: 99%
“…Current analysis showed that dominant markers may be a simple tool to achieve these aims. According to Hilsdorf (2013), the employment of dominant markers to estimate variability is common in fresh water fish and is corroborated by several recent research works in Brazilian native species (ALMEIDA et al, 2013;GOMES et al, 2011GOMES et al, , 2013JACOMETO et al, 2010;LOPERA-BARRERO et al, 2010;RAMOS et al, 2012).…”
Section: Groupingmentioning
confidence: 82%
“…Above results coupled to exclusive and fixed fragments demonstrated that even populations with low-frequency fragments have a high intrapopulation genetic variability plus a trend for genetic differentiation. Shannon´s Index and the percentage of polymorphic fragments are genetic parameters successfully employed to estimate the genetic variability of the population (ALMEIDA et al, 2013;GOMES et al, 2011GOMES et al, , 2013JACOMETO et al, 2010;LOPERA-BARRERO et al, 2010;PAULA, 2006). The analysis of molecular variance (AMOVA) between the populations revealed a greater intra-population rather than an inter-population variation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation